Cochlear potential difference between endolymph fluid and the hair cell's interior: a retold interpretation based on the Goldman equation - Sven Kurbel; Vladimir Borzan; Hilda Golem; Kristijan Dinjar (Medicinski glasnik, 2017)
Reported cochlear potential values of near 150 mV are often attributed to endolymph itself, although membrane potentials result from ion fluxes across the adjacent semipermeable membranes due to concentration gradients. Since any two fluids separated by a semipermeable membrane develop potential due to differences in solute concentrations, a proposed interpretation here is that positive potential emanates from the Reissner membrane due to small influx of sodium from perilymph to endolymph. Basolateral hair cell membranes leak potassium into the interstitial fluid and this negative potential inside hair cells further augments the electric gradient of cochlear potential. Taken together as a sum, these two potentials are near the reported values of cochlear potential. This is based on reported data for cochlear fluids used for the calculation of Nernst and Goldman potentials. The reported positive potential of Reissner membrane can be explained almost entirely by the traffic of Na+ that enters endolymph through this membrane. At the apical membrane of hair cells, acoustic stimulation modulates stereocillia permeability to potassium. Potassium concentration gradients on the apical membrane are low (the calculated Nernst value is <+3 mV), suggesting that the potassium current is not caused by the local potassium concentration gradient, but an electric field between the positive sodium generated potential on the Reissner membrane and negative inside hair cells. Potassium is forced by this overall electric field to enter hair cells when stereocilia are permeable due to mechanical bending.
Keywords: membrane potential; ion traffic; membrane permeability; labyrinth